Plant Growth-Promoting Bacteria Enhance Survival, Growth, and Nutritional Content of Sugarcane Propagated through Pre-Sprouted Seedlings under Water Deficit - Almeida, Laura Costa Oliveira [UNESP]; Santos, Hariane Luiz [UNESP]; Nogueira, Carlos Henrique de Castro [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; Silva, Gustavo Ferreira da [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP]; Silva, Marcelo de Almeida [UNESP] (MDPI, 2024)
Sugarcane plays a crucial role in global sugar and ethanol production. Conventionally, sugarcane propagation involves planting billets. However, Brazilian researchers have introduced the innovative pre-sprouted seedlings (PSS) method, widely used in the MEIOSI (Simultaneously Occurring Interrotational Method) system. Although PSS has several advantages over the conventional method, its sensitivity to water scarcity is a challenge. This study aimed to evaluate the survival and growth of PSS inoculated with Bacillus licheniformis and Bacillus subtilis (PGPB) under different water regimes. The experiment was conducted in the field in a randomized block in strips (split-block) using a 2 × 4 factorial scheme consisting of two inoculation conditions (with and without PGPB) and four water regimes (WR) (0%, 33%, 66%, and 100% of the ideal irrigation). PGPB increased PSS survival (4.17%) and water use efficiency (185.10% under the 0% WR). In addition, inoculation increased root (12.5%, 7.7%, and 16.2% for surface area, area projection, and root volume, respectively) and shoot growth. PGPB also increased nutrient uptake, such as N (60.8% and 18.3% under 0% and 66% WR), P (on average 11.7%), Mn (27.6% and 28.7% under 66% and 100% WR), Zn (111.4% under 0% WR), and Cu accumulation (27.17%), which provided a higher number of stalks per meter and, therefore, a higher multiplication rate in the MEIOSI system. Inoculation proved to be a promising alternative for PSS establishing under water restriction.
Keywords: biostimulants; growth rate; nutrition; Saccharumspp; water availability